Management of Shock in Severe Acute Malnutrition at Stabilization Centre (Medical Forum Monthly, 2021)
Objective: Early recognition and management of shock in severe acute malnutrition in children of 6 to 59 months of age.Study Design: Descriptive / Cross sectional studyPlace and Duration of Study: This study was conducted at the NSC CMC Children Hospital Larkana from October 2017 to September 2018.Materials and Methods: 691 children of age 6 months to 59 months hospitalized with SAM (weight for height <60% of median or bilateral pedal edema or MUAC <11cm) are managed in accordance to WHO guidelines. Data based on clinical features was collected and analyzed to identify risk factors associated, disease pattern and outcome.Results: In this study 691 admitted via triage/ER. Majority of them were of age between 12 months to 36 months. 280 children (40%) study population formed by marasmus, 102 children(14.5%) by kwashiorkor and 309 children (45.5%) by marasmus kwashiorkor. 37% of children had diarrhea, 39% had bronchopneumonia, 14% had pallor, 10% others. Most observed complications of SAM in our study were severe dehydration(12.44%), hypovolemic shock(11.86) and septic shock (8.3%). Patient with hypovolemic shock were managed with 15ml/kg ringer lactate i/v bolus followed by 10ml/kg Resomal, Patients with septic shock were managed with broad spectrum antibiotics and blood transfusions. Case fatality rate in our study was (3%).Conclusion: children with SAM complicated by severe dehydration, hypovolemic shock and septic shock had higher risk of death. Early detection and management of complications such as shock reduce the mortality in children with SAM.